NTRK amplification occurs frequently in pan-TRK immunopositive dedifferentiated liposarcomas - Zoltán Lippai; Gergő Papp; Károly Szuhai; Johanna Sápi; Katalin Dezső; Zoltán Sápi (Pathology and Oncology Research)
The neurotrophic tyrosine kinase receptor (NTRK) gene family is of rising importance as their fusions are oncogenic, and specific target drugs are available to inhibit the chimera proteins. Pan-TRK antibody, which shows the overexpression of the NTRK1-2-3 genes, is a useful tool to detect tumors with or without NTRK gene alterations, due to high negative predictive value. Though it is well known that pan-TRK immunopositivity is usually not connected to NTRK fusion, the role of other possible genetic alterations is under-researched. In our previous work, we found 3 NTRK1 amplified cases out of 6 cases with recurrent NTRK1 tyrosine kinase domain mutation pair, so we extended our investigation to a larger series to estimate amplification frequency. Pan-TRK immunopositivity was seen in 76 of the 132 dedifferentiated liposarcomas cases, followed by NTRK1-2-3 break-apart FISH tests in 76 pan-TRK positive cases to detect oncogenic fusions or other copy number alterations of these genes. None of the pan-TRK immunopositive dedifferentiated liposarcomas showed absolutely certain sign of fusion, however, 18 (28%) cases showed amplification of one of the genes, 13 had polysomy, 34 were normal, 11 were not evaluable. The extent of pan-TRK immunoreaction showed a positive correlation (p = 0.002) with the NTRK status found by FISH. Analyzing publicly available data from large series of 265 liposarcoma samples consisting of both well-differentiated and dedifferentiated liposarcoma case, 23 (8.6%) cases showed a mutual exclusive amplification of the NTRK genomic loci in a non-preselected, independent patient population indicating that our findings are presented in other cohorts. Our results underline the so far not revealed frequent occurrence of NTRK amplifications which might be important in the TRK inhibition therapy.